Impingement of deposited water nanodroplets with coming nanoparticles: A molecular dynamics study - Liwei Sun; Xiaojiao Zhang; Linglang Zhao; Di Lv; Keyan Lin; Yue Leng; Xiuling Wang (PLoS ONE, 2026)
Nowadays, the manipulation of water droplets has received growing interest in both academia and industry. In the current work, we aim to induce a quick sweep of deposited water droplets upon surfaces using impact nanoparticles. With the help of molecular dynamics (MD) simulations, we observe the dynamic evolution of targeted systems under different conditions. For a small value of particle’s size, deposition, wrapped bounce, and separated bounce take place as a progressive increase in particle’s velocity. The motion of a particle can be directly captured through obscuring water molecules. Moreover, the mechanisms underlying these different dynamic evolutions have been revealed through calculating kinetic energy, surface energy, and observing snapshots. In addition, we map two phase diagrams with respect to the dimensionless input kinetic energy ( E k, dim ), the diameter of the nanoparticle to that of the water droplet ( Δ ), and the intrinsic wettability of the surface ( θ sur ) to overall investigate these effects and observe all the possible outcomes. This work paves the way to understanding the progress of impingement of nanoparticles on deposited water droplets upon surfaces, which may be a good candidate for rapidly removing deposited water droplets and recovering the hydrophobicity of solid surfaces.